2023
DOI: 10.3390/polym15193956
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding of Lignin Structure Using Size-Exclusion Fractionation

Audrey LaVallie,
Anastasia A. Andrianova,
Joshua Schumaker
et al.

Abstract: The heterogeneous and recalcitrant structure of lignin hinders its practical application. Here, we describe how new approaches to lignin characterization can reveal structural details that could ultimately lead to its more efficient utilization. A suite of methods, which enabled mass balance closure, the evaluation of structural features, and an accurate molecular weight (MW) determination, were employed and revealed unexpected structural features of the five alkali lignin fractions obtained with preparative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Lignin, due to its complex structure combined with a relatively low MW, cannot be automatically assumed to occur in solutions as a near-spherical, random coil, unlike many other polymers [ 38 ]. Thus, the shape of lignin will not abide by the confinements of well-defined scatterers presented by Podzimek [ 39 ].…”
Section: Radius Of Gyration Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lignin, due to its complex structure combined with a relatively low MW, cannot be automatically assumed to occur in solutions as a near-spherical, random coil, unlike many other polymers [ 38 ]. Thus, the shape of lignin will not abide by the confinements of well-defined scatterers presented by Podzimek [ 39 ].…”
Section: Radius Of Gyration Measurementsmentioning
confidence: 99%
“…Coupling a SEC column to a mass spectrometer with appropriate ionization techniques has been a recent trend in the analysis of biomass-derived products [ 63 , 64 , 65 ]. Nonetheless, the bias towards lower MW fragments should be taken into account since ionization and vaporization of larger MW species is hindered [ 38 ]. The benefit of MS detection is that characteristic ions of the analyte can be identified while providing a mass distribution [ 66 ].…”
Section: Coupling Fractionation With Multi-angle Light Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they found that derivatization reactions may skew the results, distorting the determined MW toward higher values . Recently, several studies reported methods employing silica-based stationary phases with more polar eluents such as DMSO and DMF using salt additives. , Nevertheless, THF-based GPC with PS-calibration is still a commonly employed method. …”
Section: Introductionmentioning
confidence: 99%
“… 18 , 19 Nevertheless, THF-based GPC with PS-calibration is still a commonly employed method. 20 23 …”
Section: Introductionmentioning
confidence: 99%